Flying-Qubit Control: Basics, Progress, and Outlook - Wenlong Li; Huanying Sun; Yulong Liu; Tiefu Li; Re-Bing Wu (Advanced Devices & Instrumentation)
Flying qubit is one type of the basic elements for transmitting quantum information in quantum networks. It can serve as a communication link between quantum computer nodes and represents a vital part of secure data transmission. For high-fidelity information transmission, precise control of flying qubit is highly demanded. Here, based on quantized photons or phonons as the carriers of the flying qubit, we review the basics and the progress of the flying-qubit control in both theoretical and experimental aspects. The flying-qubit control system can be regarded as an open quantum system with [Formula: see text] energy levels coupled with multiple quantum channels. Its input includes classical components, such as coherent or incoherent control functions, as well as quantum components, but its output only includes quantum components, and the system is affected by environmental noise. According to the characteristics of quantum input and quantum output fields, the flying-qubit control problems can be divided into 3 categories: generation, reception, and conversion. From a theoretical perspective, the different modeling approaches of the flying-qubit control are discussed and compared, including the master equation, the quantum trajectory, the scattering matrix, the quantum stochastic differential equation, and the quantum Langevin equation. Considering both control design schemes and experimental perspectives, various control strategies and experimental progress have been thoroughly discussed and analyzed. The applications and future directions of flying-qubit control are discussed. The realization of flying qubits plays a vital role in application scenarios such as quantum coherent interconnection, the construction of large-scale quantum chips with a large number of bits, and the link between computers and communication networks.